Learning pedestrian’s perspective towards sidewalk through new urbanism - Mandasari, Veronica (Journal of Placemaking and Streetscape Design, 2024)
In the 1990s, several urban and environmental designers discussed various issues related to suburban expansion, including income disparities, environmental degradation, and rampant use of motorized vehicles. The New Urbanism movement became known in the 1970s and 1980s in America. The principles of New Urbanism are clearly illustrated in the book Charter of the New Urbanism (Leccese & McCormick, 2000). The nature of being friendly to pedestrians is one form/pattern of the theory of New Urbanism. New Urbanism is also known as neotraditional design, transit-oriented development, and traditional or neighborhood development (TND). The analysis technique used for this goal is IPA (Important Performance Analysis). Before conducting the analysis process, it is necessary to test the validity and reliability and the Wilcoxon test of the variables used. The study focuses on the Tunjungan area in Surabaya City, an essential element of accessibility for trade and service areas. A pedestrian network is necessary for safe and comfortable mobility, as mandated by the Regulation of the Minister of Public Works. TOD nodes were created to connect public and private transportation and link neighborhoods and districts through corridors. These corridors are essential in developing New Urbanism theory, which recommends corridors with mixed land use patterns to create a compatible environment and protect public security, health, and safety. Community participation is necessary to develop regulations related to corridors.